Integration of Islamic Values and Digital Technology in Islamic Education in The Digital Era - Nuraini, Mustika Efika; Shohib, Muhammad Wildan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines efforts to integrate Islamic values with the use of digital technology in Islamic Religious Education in the digital era. The focus of the study is on the role of technology in supporting the internalization of faith, morals, and spirituality among students, as well as identifying various challenges that arise in the implementation of value-based digital learning. This study uses a qualitative approach through the Systematic Literature Review (SLR) method by analyzing scientific publications from 2021 to 2026 obtained from academic databases such as Google Scholar, DOAJ, and accredited national journals. The analysis was conducted through thematic synthesis to map conceptual trends, pedagogical approaches, and issues related to the integration of Islamic values and digital technology. The results of the study show that effective integration requires a balance between strengthening digital literacy and internalizing Islamic values, implementing human-centered and ethics-based learning, and strengthening the role of educators as value guides. The main challenges identified include a technocratic orientation of learning, limitations in educators' pedagogical and digital literacy competencies, the influence of a digital environment that is not in harmony with Islamic values, and the lack of a systematic conceptual framework. This study emphasizes the importance of developing a value-based conceptual model as a foundation for strengthening Islamic religious education that is adaptive to technological developments and oriented towards shaping the character of students